Prevalence and real-world management of vedolizumab-associated enthesitis in successfully treated IBD patients. (12th February 2021) - Ruscio, Mirko Di; Tinazzi, Ilaria; Variola, Angela; Geccherle, Andrea; Marchetta, Antonio; McGonagle, Dennis
Abstract: Background: Some studies have reported the development of moderate and severe de novo SpA-associated disease under vedolizumab (VDZ) treatment for IBD. Herein, we report a case series who developed severe enthesitis under VDZ therapy from a cohort of 90 treated cases. Methods: In a single Italian IBD Unit in which 90 cases were on VDZ therapy, we identified 11 cases who developed severe enthesitis. The onset of disease in relationship to VDZ initiation, clinical and sonographic imaging features, and outcomes (including therapy switches) was described. Results: A total of 11 cases, including 8 prior anti-TNF failures, with new-onset entheseal pathology were identified: multifocal ( n = 4), unifocal ( n = 6), and enthesitis/synovitis/dactylitis ( n = 1). The mean duration of symptoms was 46 weeks (range 6–119), the mean CRP was 5.1 mg/dl, and the majority were HLA-B27 negative and showed good clinical response for gut disease. Clinical features and US showed severe enthesitis, including power Doppler change in 7 patients. All patients were initially treated with NSAIDs, and 5 patients underwent local steroid injections. At 12 months, 5/7 cases continued VDZ and 2 were switched to ustekinumab. At 12 months follow-up of 7 cases, 5 patients were in clinical remission and 2 patients had mild enthesitis with minimal increase of power Doppler signal. In addition, 4/7 severe patients developed marked post-inflammatory entheseal calcifications Conclusions: A predominant isolated severe enthesitis pattern of SpA may develop under VDZ therapy with severe disease in 8% of cases. Most cases continued VDZ therapy.